Epidemiological characters and the use of cluster analysis for characterizing partial resistance to soybean rust - Santos, Juliana Araújo; Juliatti, Fernando Cézar; Santos, Verônica Araújo; Polizel, Analy Castilho; Juliatti, Fernanda Cristina; Hamawaki, Osvaldo Toshiuki (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate the partial resistance of soybean genotypes against Phakopsora pachyrhizi. Resistance characteristics were: average number of pustules, rust severity and the area under the disease progress curve. Significant differences were found among the genotypes for the average number of pustules and rust severity. Multivariate analysis allowed the discrimination of partially resistant genotypes. Three genotypes (G4, G41, and G42), referring to parents Cristalina and IAC 100, presented greater partial resistance to soybean rust.